Analisis Peran Audit Internal Terhadap Kualitas Laporan Keuangan Berdasarkan Literature Review Terindeks Sinta - Iis Nurlela; Yenyen Susilawati; Shopi Sherima; Nunung Nuraeni; Santoso Santoso (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to examine the role of internal auditors in financial reporting quality. Financial reporting is an important aspect considered in decision-making processes. The role of internal audit is highlighted as having a significant impact on improving the quality of financial reports. The method applied in this research is qualitative descriptive method using literature review. Based on the analysis results of this study, it is shown that internal audit plays a role in the quality of financial reporting in companies.